Fault diagnosis scheme for open-circuit faults in field-oriented control induction motor drives - Espinoza Trejo, Diego Rivelino (2013)
In this study, a new model-based fault detection and isolation (FDI) strategy is proposed for field-oriented control (FOC) induction motor (IM) drives. Actuator faults are addressed, and specifically, single open-circuit faults are considered in this study. The residual signals are synthesised by taking the resulting closed-loop dynamics when a FOC strategy is applied, that is, the residuals are referenced to the synchronous reference frame (dqe-coordinates), which are generated by using a bank of variable structure observers to obtain a robust FDI scheme. Thus, subsystems sensitive to a specific fault, but decoupled from other faults are obtained in a natural way, where only two stator currents and the mechanical position are required for fault isolation purposes. Residual evaluation is carried out in the stator reference frame (dq-coordinates) for the IM model, where the residual direction (angle) is employed to isolate a fault in each one of the six power switches in a voltage source inverter. In addition, the observer FDI scheme can be combined with a fault re-configuration strategy in order to improve the reliability of the motor drive. Experimental results are illustrated for a three-phase 3/4 HP IM drive at different reference frequencies and load torques with single open-circuit faults that verify the ideas presented in this work.